2003
DOI: 10.2989/10220110309485793
|View full text |Cite
|
Sign up to set email alerts
|

Soil and vegetation changes across a Succulent Karoo grazing gradient

Abstract: This study describes soil and vegetation changes radiating out from a central watering point on a livestock farm in the SucculentCeres Karoo (Tanqua). The aim was to identify possible relationships between long-term grazing pressure, and soil and vegetation properties. There are indications that continuous high-intensity defoliation of Succulent Karoo vegetation leads to a decline in species richness and perennial plant cover with a consequent loss of fertile topsoil. Over-grazed areas close to the watering po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Furthermore, managed grazing is the single most extensive form of land use on the planet (Asner et al 2004). Even for extensive systems where rotational grazing is not practiced, there are still important issues of animal concentration around water holes and camping areas where animals congregate (Beukes and Ellis 2003;Betteridge et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, managed grazing is the single most extensive form of land use on the planet (Asner et al 2004). Even for extensive systems where rotational grazing is not practiced, there are still important issues of animal concentration around water holes and camping areas where animals congregate (Beukes and Ellis 2003;Betteridge et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…1994; Jeltsch et al . 1997; Thrash 1998a,b) and a pair of unreplicated studies from the Succulent Karoo (Beukes & Ellis 2002; Riginos & Hoffman 2003). To date, no published studies have assessed the impact of watering point provision on the structure and species richness of Nama‐Karoo shrublands in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Soil compaction alters soil structure and hydrology which can affect water absorption by plants (Kozlowski, 1999). Depending on the intensity and period of livestock stocking rates these factors can cause vegetation change, as has been observed along a piosphere in the Tanqua Karoo part of the Succulent Karoo biome (Beukes and Ellis, 2003). Haarmeyer et al (2010) found that intense stocking of livestock reduced species richness and the abundance of endemic species on quartz field vegetation.…”
Section: Introductionmentioning
confidence: 97%